Editorial Sir John Houghton. Issue 4 (3rd April 2021) - Cracknell, Arthur P.; Varotsos, Costas A.
ABSTRACT: The death of Sir John Houghton a few months ago revived memories of pioneering figures who have left an indelible signature on the science of remote sensing. This article summarizes the main contributions of this scientist's work, which include, among others, the foundation of remote sensing - especially in early satellite technology- the selective chopper radiometer, the atmospheric sounding, the clouds classification, the weather satellites and the radiative interaction of the land and the atmosphere.